UJI MASA SIMPAN KUALITAS MINYAK HASIL EKSTRAKSI BIJI BUAH BINTARO (Cerbera manghas L) SEBAGAI BAHAN BAKU BIODIESEL - Ponco Prabowo; Rudianda Sulaeman; Evi Sri Budiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Saving bintaro oil can make damage because hidrolysis and oxidation process. Demage oil could know by increasing of free fatty acid degree and water content degree. Storage time influence quality of bintaro seeds extraction oil for biodiesel material. This research using Randomized Complete Block Design (RCBD) consist of five (5) treatmens and three (3) replication. The result of research showed quality of bintaro oil is influenced by storage time. If storage time is longer, quality of bintaro oil will be low. During storage time, free fatty acid degree of bintaro oil had increased. The oil with A0 treatment including refined oil, the oil with A1 treatment including low free fatty acid oil and the oil with A2 (14 days), A3 (21 days), A4 (28  days) treatment including high free fatty acid oil.Keywords : storage time, bintaro seeds extraction, biodiesel material